A Socio-Family Matriciality No Social Work with Families No Scope of Suas: Dilemmas and Perspectives - Rafael Frederico (International Journal of Science and Society, 2020)
This article aims to reflect on the Matricialidade Sociofamiliar in Social Work with families in the context of Social Assistance. For this, we used bibliographic research and field. Identifies that the Matricialidade Sociofamiliar is a contradictory concept, you can blame the families for the protection of its members, or hold the State by social protection.